2020
DOI: 10.1016/j.mayocp.2020.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Safety Update

Abstract: Objective To provide an update on key safety metrics after transfusion of convalescent plasma in hospitalized coronavirus 2019 (COVID-19) patients, having previously demonstrated safety in 5000 hospitalized patients. Patients and Methods From April 3 to June 2, 2020, the US Food and Drug Administration Expanded Access Program for COVID-19 convalescent plasma transfused a convenience sample of 20,000 hospitalized patients with COVID-19 convalescent plasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
114
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(126 citation statements)
references
References 21 publications
9
114
1
2
Order By: Relevance
“…10 The authors of the safety update on the first 20 000 recipients said their results provided "robust evidence that transfusion of CP [convalescent plasma] is safe." 11 However, close examination reveals that adjudication of the "relatedness" of serious adverse thrombotic and cardiac events was conducted by the treating physician, with no defined protocol and no independent review. 11 Most of the 677 cardiac events (88.2%) and 113 thrombotic events (66.3%) were judged not to be related to transfusion, and these events were therefore excluded from the reported adverse event rates.…”
mentioning
confidence: 99%
“…10 The authors of the safety update on the first 20 000 recipients said their results provided "robust evidence that transfusion of CP [convalescent plasma] is safe." 11 However, close examination reveals that adjudication of the "relatedness" of serious adverse thrombotic and cardiac events was conducted by the treating physician, with no defined protocol and no independent review. 11 Most of the 677 cardiac events (88.2%) and 113 thrombotic events (66.3%) were judged not to be related to transfusion, and these events were therefore excluded from the reported adverse event rates.…”
mentioning
confidence: 99%
“…However, this trial was terminated early and therefore the sample was insufficient to determine subtle clinical differences among the treatment arms [48]. In addition, a safety analysis conducted on 20,000 patients who received convalescent plasma through the National Extended Access Program revealed that although adverse events were uncommon (<1%), they did include transfusionassociated circulatory overload (TACO), transfusion-related acute lung injury (TRALI), allergic reactions, and death [49].…”
Section: Immune-based Therapiesmentioning
confidence: 99%
“…33 The trial was further expanded to over 20,000 patients and the latest update demonstrated a mortality rate of 8.6%, which was far less than the previous findings of 14.9%. 34 Although these trials successfully demonstrated the safety of CP therapy, its efficacy was not studied. These trials also lacked a control arm against which to compare the findings.…”
Section: Outcomes Of Cp Therapy In Covid-19 Trialsmentioning
confidence: 99%